A Note on Income Velocities - Currie, Lauchlin (Quarterly Journal of Economics, 1934)
Journal Article A Note on Income Velocities Get access Lauchlin Currie Lauchlin Currie Harvard University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 48, Issue 2, February 1934, Pages 353–354, https://doi.org/10.2307/1885614 Published: 01 February 1934